Niwelowanie dysproporcji w rozwoju polskiego transportu morskiego jako jeden ze strategicznych celów polityki w wymiarze mezoekonomicznym - Brózda, Joanna (Leveling of Disproportion in Development of Polish Mari time Transportation as One of the Strategic Targets of Policy in Mesoeconomic Dimensio, 2006)
Development of Polish transport since postwar till present day has been proceeding under influence of many different factors. Currently its characteristic feature is unbalanced branch structure. In case of maritime transport one can notice: that its significance in Polish sea trade and carrying transit cargo is decreasing, that it has obsolete infrastructure, does not have adequate infrastructure for multimodal transport and that there is taking place progressive decapitalization process of sea harbours' properties. From the other hand Polish merchant fleet within the space of last dozen or so years has decreased by more than half, and this tendency is accompanied by movements of ship owners under foreign flags. Additionally the average age of cargo carrying sea fleet in Poland is very high. One can easily notice specific disproportion between condition of maritime transport in Poland and in highly developed countries of European Union there are. Foregoing elaboration is devoted to present those problems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 185-196